Bibliometric Analysis of the Development of Women's Entrepreneurship Literature in Indonesia - Loso Judijanto; Arief Yanto Rukmana; Maryam Maryam; Bagus Prabowo; Vera Selviana Adoe (West Science Journal Economic and Entrepreneurship, 2025)
Women’s entrepreneurship has gained recognition as a critical factor in promoting inclusive economic development, particularly in emerging economies such as Indonesia. This study presents a bibliometric analysis of scholarly publications on women’s entrepreneurship, focusing on trends, thematic structures, and collaboration networks from 2000 to 2025. Using data retrieved from the Scopus database and analyzed through VOSviewer, the study maps co-authorship patterns, co-citation networks, keyword co-occurrence clusters, and temporal evolution of research themes. The findings highlight dominant scholars, countries, and themes such as gender roles, empowerment, entrepreneurial intention, and sustainability. The overlay and density visualizations indicate a growing shift toward system-level and empowerment-related topics in recent years. However, the analysis also reveals underrepresentation of Indonesian research in global discourse. The study concludes by recommending greater international collaboration, diverse methodologies, and deeper contextual engagement to enrich the field and inform effective policy interventions.